Kinship does not predict the structure of a shark social network. (17th February 2021) - Mourier, Johann; Planes, Serge
Abstract: Genetic relatedness in animal societies is often a factor that drives the structure of social groups. In the marine world, most studies which have investigated this question have focused on marine mammals such as whales and dolphins. For sharks, recent studies have demonstrated preferential associations among individuals from which social communities emerge. Assortment patterns have been found according to phenotypic or behavioral traits, but the role of genetic relatedness in shaping the social structure of adult shark populations has, to the best of our knowledge, never been investigated. Here, we used a social network analysis crossed with DNA microsatellite genotyping to investigate the role of the genetic relatedness in the social structure of a blacktip reef shark ( Carcharhinus melanopterus ) population. Based on the data from 156 groups of sharks, we used generalized affiliation indices to isolate social preferences from nonsocial associations, controlling for the contribution of sex, size, gregariousness, spatial, and temporal overlap on social associations, to test for the influence of genetic relatedness on social structure. A double-permutation procedure was employed to confirm our results and account for issues arising from potentially elevated type I and type II error rates. Kinship was not a predictor of associations and affiliations among sharks at the dyad or community levels as individuals tended to associate independently of the genetic relatedness among them. The lack of parental care in this species may contribute to the breakdown of family links in the population early in life, thereby preventing the formation of kin-based social networks. Abstract : Little is known about the role of genetic relatedness in structuring shark populations. We investigated the role of kinship in the social structure of a blacktip reef shark population. Kinship was not a predictor of shark associations either at the dyad or community levels. The lack of parental care in this species may prevent the formation of kin-based social networks.